Strategi manajemen konflik dalam menjaga toleransi antar karyawan berbeda agama dan budaya - Al Ghifari, Azam (Maliki Interdisciplinary Journal, 2026)
This study aims to understand conflict management strategies in managing tolerance amongst employees who have different religious and religious beliefs in the workplace. The research methodology used is kualitatif deskriptif using data collection techniques through observation, documentation, and wawancara. The study's findings indicate that disagreements among employees are typically caused by differences in communication styles, pandangan, and religious beliefs. In order to resolve this conflict, the company uses a strategy that includes media, musyawarah, terbuka communication, as well as tolerance and keberagaman. In addition, businesses may provide dukungan through policies that support religious and religious beliefs. The aforementioned strategy is effective in creating harmonious work relationships, increasing employee satisfaction, and fostering an inclusive and supportive work environment for all employees in the organization.